The incorporation of AlScN ferroelectric gate dielectric in AlGaN/GaN-HEMT with polarization-modulated threshold voltage. (7th March 2023) - Zhao, Zihui; Dai, Yijun; Meng, Fanping; Chen, Li; Liu, Kunzi; Luo, Tian; Yu, Zhehan; Wang, Qikun; Yang, Zhenhai; Zhang, Jijun; Guo, Wei; Wu, Liang; et al.
Abstract: In this work, the insertion of AlScN ferroelectric gate dielectric on the performance of the AlGaN/GaN HEMT device is investigated. With negative pre-poling on AlScN, the threshold voltage ( V th ) of the device shifts positively with a swing range of 3.26 V. The influence of polarization modulation is also reflected by the suppression of gate leakage and the reduction of the subthreshold swing of the device. The AlScN-integrated GaN HEMT exhibits an on/off ratio of 10 6 and a subthreshold swing of 80 mV dec −1 . The depletion mechanism of 2DEG at the AlGaN/GaN interface was well described by a TCAD model.